2018
DOI: 10.7150/jca.23087
|View full text |Cite
|
Sign up to set email alerts
|

LASS2 regulates invasion and chemoresistance via ERK/Drp1 modulated mitochondrial dynamics in bladder cancer cells

Abstract: Mitochondria coordinated a lot of vital cellular processes of energy production and distribution. Change of mitochondrial functions has been implicated in cancer progression. The present study aims to investigate the involvement of mitochondria dynamics in LASS2 induced invasion and chemoresistance of bladder cancer cells. J82 and BIU87 cell lines were used for LASS2 plasmid transfection while siRNA knockdown was carried out in 5637 cell line. Matrigel invasion assay and Annexin V/PI staining demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Another study also elucidated the role of ERK-induced DRP1 phosphorylation in the chemoresistance of bladder cancer cells. The study reported that LASS2 inhibits bladder cancer invasion and chemoresistance through the regulation of ERK-DRP1-induced mitochondrial fission [ 90 ].…”
Section: Role Of Mitochondrial Remodeling (Fusion Fission Mitophagy and Transfer) In Cancer Chemoresistancementioning
confidence: 99%
“…Another study also elucidated the role of ERK-induced DRP1 phosphorylation in the chemoresistance of bladder cancer cells. The study reported that LASS2 inhibits bladder cancer invasion and chemoresistance through the regulation of ERK-DRP1-induced mitochondrial fission [ 90 ].…”
Section: Role Of Mitochondrial Remodeling (Fusion Fission Mitophagy and Transfer) In Cancer Chemoresistancementioning
confidence: 99%
“…Previous studies demonstrated that activation of the AKT [ 71 , 72 , 73 ] and ERK [ 73 , 74 , 75 ] signaling is involved in mediating drug resistance and also linked to the upregulation of anti-apoptotic proteins such as XIAP [ 76 ]. We previously also found that paclitaxel-induced survivin expression is through activation of the PI3K-AKT and MEK-ERK1/2 pathways as the paclitaxel-resistant factor, and the inhibition of these two pathways by their specific inhibitors decreased survivin expression and sensitized paclitaxel efficacy in breast cancer cells [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of CerS-2 on BC invasion and chemoresistance is partly dependent on Drp1 signaling. CerS-2 can inhibit Drp1 signaling through regulation of ERK pathway [13]. Two genes closely related to cancer metastasis, called MMP-2 and MMP-9, had higher activities in BC cells knocked down for CerS-2 [12].…”
Section: Bladder Cancer (Bc)mentioning
confidence: 99%